Lower limb joint kinetics during the first stance phase in athletics sprinting: three elite athlete case studies - Bezodis, N. E.; Salo, A. I. T.; Trewartha, G. (Journal of Sports Sciences, 2014)
This study analysed the first stance phase joint kinetics of three elite sprinters to improve the understanding of technique and investigate how individual differences in technique could influence the resulting levels of performance. Force (1000 Hz) and video (200 Hz) data were collected and resultant moments, power and work at the stance leg metatarsal-phalangeal (MTP), ankle, knee and hip joints were calculated. The MTP and ankle joints both exhibited resultant plantarflexor moments throughout stance. Whilst the ankle joint generated up to four times more energy than it absorbed, the MTP joint was primarily an energy absorber. Knee extensor resultant moments and power were produced throughout the majority of stance, and the best-performing sprinter generated double and four times the amount of knee joint energy compared to the other two sprinters. The hip joint extended throughout stance. Positive hip extensor energy was generated during early stance before energy was absorbed at the hip as the resultant moment became flexor-dominant towards toe-off. The generation of energy at the ankle appears to be of greater importance than in later phases of a sprint, whilst knee joint energy generation may be vital for early acceleration and is potentially facilitated by favourable kinematics at touchdown.